The influence of coaching on perceived job performance of newly promoted managers - Maila, Hudson (My University, 2016)
The perceptions held by newly promoted managers or those managers who have moved between managerial roles, when it comes to their own job performance in the workplace, remain interesting. An exploratory research design method was followed with the aim of providing evidence-based literature in order to explore how coaching can influence the perceived job performance of these managers, considering the amount of effort needed from them to adjust to their roles. The study was conducted using a convenience non-probability sample of managers who are working in different sectors ranging from public utilities, the media as well as engineering and gas industries. Data were collected from the research participants who were readily available and transcripts were produced. In order to maintain accuracy, the transcripts were based on recordings of the outcomes of semi-structured, one-on-one interviews conducted using a research interview discussion guide. A triangulation process to collect data from different sources was used, focusing on managers who received coaching and managers who did not receive coaching, as well as the managers managing the aforesaid categories of managers. The data collected were transcribed and then analysed using Atlas.ti software, based on themed content analysis. The results provide a South African perspective on the perceived influence of coaching on newly promoted managers or those managers who have moved between managerial roles. The findings demonstrated that coaching can contribute positively to the role transition and work adjustment of these managers, as one of the managers who had been coached indicated, saying, “It assisted me in affirming myself in the role.” The meaning attached to the findings is that coaching can contribute towards building the necessary confidence to lead and manage others. However, the lack of a common criterion for measuring successful job performance, focusing on specific managerial competencies, remains a challenge. The research participants in this study took up coaching for different reasons and the level of impact was thinly spread across these dimensions. Therefore, more scientific research still need to be done to get empirical evidence on the impact of coaching on perceived job performance in a South African context, using a common criterion and specific managerial competencies.
Keywords: Executive coaching--South Africa; Employees--Coaching of--South Africa; Performance--Management